PENDIDIKAN PLURALIS-TOLERAN DI LINGKUNGAN KELUARGA NGADAS PONCOKUSUMO MALANG - Aunia Ulfah; Mohammad Asrori; M. Fahim Tharaba Tharaba (Universitas Islam Lamongan, 2022)
Ngadas is one of the villages that are strong in maintaining the customs of the Tengger Tribe. This village has followers of various religions, Buddhism, Islam, and Hinduism. The reality of this village's religious differences can become a source of conflict for the community if it is not appropriately managed. This study aims to describe the concept and form of pluralist-tolerant education in the Ngadas family. The qualitative approach and the type of case study research are used in this research. The research found that the concept of pluralist-tolerant education in the family environment in Ngadas is education that opens a vision to a broader horizon regardless of group, ethnicity, or cultural and religious traditions to realize universal brotherhood in line with Islamic teachings. This pluralist-tolerant education is carried out in an informal and early form. Meanwhile, the implications of the practice of Islamic education in the Ngadas village family are respecting the beliefs of others and acknowledging the existing religious reality.